Effect of orientation and configuration of ZnO nanorods on electrical conductivity prepared through hydrothermal method on suspended substrate - Iqbal, Younas; Mustafa, M.K.; Muhammad Rosdi, N.L. (UTHM Publisher, 2016)
Hexagonal oriented and dumbbell shaped ZnO nanorods were prepared through hydrothermal method on gold coated glass substrate suspended in growth solution at various precursors concentrations. Tower and dumbbell shaped ZnO nanorods were observed on the substrates. The morphology, crystalline structure, and electrical conductivity of the synthesized ZnO nanorods were observed through Field emission scanning electron microscopy (FESEM), X-rays diffraction (XRD) and four point probe. Each sample consists of ZnO nanorods having various direction of orientation. The FESEM, XRD and Four point probe studies reveals that the orientation and configuration of ZnO nanorods has a significant effect on the electrical conductivity. ZnO nanorods with well hexagonal shape and orientation has the better electrical conductivity (10688 seimens/meter, 7022.2 seimens/meter and 8238 seimens/meter) then the dispersed and congested nanorods.